Natural Occurrence of Aflatoxins Contamination in Commercial Spices in Iran - Maryam Jalili (Iranian Journal of Health, Safety and Environment, 2016)
A total of 80 sample of spices (red pepper, black pepper, turmeric and cinnamon), commercialized in Iran, was analyzed for aflatoxins B1, B2, G1 and G2 content using high-performance liquid chromatography (HPLC) with a fluorescence detector (FD). A mixture of acetonitrile–methanol–water (17:29:54; v/v) was used as the mobile phase and an immunoaffinity column (IAC) applied as a cleanup method. All kinds of spice samples were spiked with aflatoxins B1, B2, G1 and G2 at levels of 1, 10, and 30 ng/g and recovery values were determined. Results showed recoveries ranged from 76.4±5.6 to 98.3±3.2 for AFG1 in cinnamon (spiked at 1ng/g) and AFB2 in turmeric (spiked at 10ng/g) respectively. Thirty-two out of 80 (40%) samples were contaminated with aflatoxins ranged from 0.85±0.10 to 24.60±0.12. Aflatoxin B1 was detected in all of the contaminated samples at the highest concentration as compared with other aflatoxins. Red pepper was significantly (p≤0.05) more contaminated than other spices.